mWorld: A multiuser 3D virtual environment - Dias, J. M. S.; Galli, R.; Almeida, A. C.; Belo, C. A. C.; Rebordão, J. M. (IEEE Computer Graphics and Applications, 1997)
mWorld integrates 3D virtual-scene generation tools and synchronous, asynchronous, and time-dependent data communication techniques to enable cooperative 3D design and visualization across networks.